2012
DOI: 10.1016/j.socscimed.2012.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs among disabled elderly Malaysians

Abstract: Unmet need as a significant factor affecting quality of life in later life has recently received considerable attention in gerontological research. The main aim of this study was to identify the prevalence, predicting factors, and negative consequence of unmet need among older Malaysians. The findings may be useful to reduce unmet need and the burden of its adverse consequence. The sample for this study consists of 400 functionally disabled elderly people aged 60 and over was obtained from a large national sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 24 publications
2
55
3
Order By: Relevance
“…Older men (compared to women) are more likely to benefit from tangible support, whereas older women gain advantage through emotional support from their social environment. This premise is supported by studies which found that older men were at risk of experiencing unmet needs when there is a lack of tangible support for their physical care 41. However, among older women, greater levels of emotional support are found to be important in reducing depression and boosting psychological well-being 17,39.…”
Section: Discussionmentioning
confidence: 90%
“…Older men (compared to women) are more likely to benefit from tangible support, whereas older women gain advantage through emotional support from their social environment. This premise is supported by studies which found that older men were at risk of experiencing unmet needs when there is a lack of tangible support for their physical care 41. However, among older women, greater levels of emotional support are found to be important in reducing depression and boosting psychological well-being 17,39.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to the mass media, several gerontological studies reinforce, rather than challenge, such ageist stereotypes 2. For example, the studies focusing on changes in physical and cognitive functioning of elderly people have extremely portrayed old age as a period of losses, loneliness, and declining physical and cognitive functioning 9–11…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that low educational attainment, low income, not being currently married, living alone, severe ADL disability, cognitive impairment, and unavailability and unaffordability of services were significantly associated with unmet LTC needs [8,13,[16][17][18]. Other studies have found differences between urban and rural residents.…”
Section: Introductionmentioning
confidence: 99%